Analysis of court decisions implementation on state confiscated assets for asset recovery optimization - Fany Kartika; Nur Anis Hidayah; Firamita Yuliasari; Mungki Hadipratikto (Integritas: Jurnal Antikorupsi, 2025)
The optimization of asset recovery is a key component of the Anti-Corruption System Strengthening Program within the National Strategy and is mandated in the National Long-Term Development Plan (RPJPN) 2025–2045, implemented by the Corruption Eradication Commission (KPK). The execution of court decisions on assets of convicted persons categorized as “Confiscated for the State” can be carried out through two mechanisms: auction or Determination of Usage Status (PSP)/grant. Data indicate that assets in the category of land and buildings executed through the PSP/grant mechanism contribute more significantly to asset recovery compared to those executed through auctions. This study employs descriptive and predictive analysis. The descriptive analysis is used to explain phenomena and identify the underlying factors that lead to higher asset recovery contributions from the PSP/grant mechanism. Furthermore, this study proposes predictive modeling for executing confiscated assets using regression, Naïve Bayes, and Decision Tree methods through RapidMiner. These models can serve as decision-support tools for stakeholders in determining whether confiscated inventory assets should be executed through auction or PSP/grant mechanisms, as well as in forecasting potential future revenues and asset recovery outcomes.